2020
DOI: 10.1007/s10198-020-01213-9
|View full text |Cite
|
Sign up to set email alerts
|

Using machine learning to assess the predictive potential of standardized nursing data for home healthcare case-mix classification

Abstract: Background The Netherlands is currently investigating the feasibility of moving from fee-for-service to prospective payments for home healthcare, which would require a suitable case-mix system. In 2017, health insurers mandated a preliminary case-mix system as a first step towards generating information on client differences in relation to care use. Home healthcare providers have also increasingly adopted standardized nursing terminology (SNT) as part of their electronic health records (EHRs), providing novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Examples include short-term care for frail elderly and chronically ill (<3 months), care for terminally ill patients, and care for children. The decision tree for allocation to a single care category can be found in a recent study by De Korte et al 18…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Examples include short-term care for frail elderly and chronically ill (<3 months), care for terminally ill patients, and care for children. The decision tree for allocation to a single care category can be found in a recent study by De Korte et al 18…”
Section: Methodsmentioning
confidence: 99%
“…Table 2 lists all planned combinations. Previous work on similar data showed that there are clients with either a comparatively low care use (defined as <4 hours during a care episode) or high care use (defined as >40 hours per 4 weeks care episode or >120 hours per 13 weeks episode) 18. It is not uncommon to exclude such clients from a prospective payment system based on casemix classification and instead to reimburse their care based on, for example, FFS 34.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations